Florid Cemento Osseous Dysplasia - K Sarala (Journal of Indian Academy of Oral Medicine and Radiology, 2006)
Florid Cemento Osseous Dysplasia (FCOD) is a condition in which diffuse asymptomatic radiopaque and radiolucent intra osseous areas of cementoosseous tissue occurs involving one or both arches. It is most often seen in middle-aged African American women. A 50 year old patient with painless multiple radiopaque lesions bilaterally in both jaws is presented its clinical, radiographic histological features and a brief review of literatures are discussed.